Integrated morphological, metabolome, and transcriptome analyses revealed the mechanism of exogenous gibberellin promoting petiole elongation in Oenanthe javanica - Feng, Kai; Li, Xibei; Yan, Yajie; Liu, Ruozhenyi; Li, Zixuan; Sun, Nan; Yang, Zhiyuan; Zhao, Shuping; Wu, Peng; Li, Liangjun (Frontiers in Plant Science, 2023)
Oenanthe javanica (Blume) DC. is a popular vegetable with unique flavor and its leaf is the main product organ. Gibberellin (GA) is an important plant hormone that plays vital roles in regulating the growth of plants. In this study, the plants of water dropwort were treated with different concentrations of GA3. The plant height of water dropwort was significantly increased after GA3 treatment. Anatomical structure analysis indicated that the cell length of water dropwort was elongated under exogenous application of GA3. The metabolome analysis showed flavonoids were the most abundant metabolites and the biosynthesis of secondary metabolites were also regulated by GA3. The exogenous application of GA3 altered the gene expressions of plant hormone signal transduction (GID and DELLA) and metabolites biosynthesis pathways to regulate the growth of water dropwort. The GA contents were modulated by up-regulating the expression of GA metabolism gene GA2ox. The differentially expressed genes related to cell wall formation were significantly enriched. A total of 22 cellulose synthase involved in cellulose biosynthesis were identified from the genome of water dropwort. Our results indicated that GA treatment promoted the cell elongation by inducing the expression of cellulose synthase and cell wall formation in water dropwort. These results revealed the molecular mechanism of GA-mediated cell elongation, which will provide valuable reference for using GA to regulate the growth of water dropwort.